The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1183/13993003.02276-2021
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of pulmonary arterial hypertension in Italy in the COVID-19 era: is risk of disease progression around the corner?

Abstract: ObjectiveThe coronavirus disease-2019 (COVID-19) oubreak has led to significant restrictions on routine medical care. We conducted a multicenter nationwide survey of PAH patients aiming at determining the consequences of the Governance measures on PAH management and risk of poor outcome in patients with COVID-19.Meterials and MethodsDemographic data, number of in-person visits, 6-min walk and echocardiographic tests, BNP/NT-proBNP tests, WHO functional class assessment, presence of elective and non-elective ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…The risk of death due to COVID‐19 among PAH/CTEPH patients is much higher compared to the general population. In the first months of the pandemic, March–May 2020, the mortality rate due to COVID‐19 among PAH/CTEPH patients was reported to be around 45% 13,29 ; in subsequent months the rate was 8%–22% 8–12 . According to various authors, 30%–81% of PAH/CTEPH patients required hospitalization due to COVID‐19 8–13,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of death due to COVID‐19 among PAH/CTEPH patients is much higher compared to the general population. In the first months of the pandemic, March–May 2020, the mortality rate due to COVID‐19 among PAH/CTEPH patients was reported to be around 45% 13,29 ; in subsequent months the rate was 8%–22% 8–12 . According to various authors, 30%–81% of PAH/CTEPH patients required hospitalization due to COVID‐19 8–13,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic thromboembolic pulmonary hypertension (CTEPH) belongs to group 4 of clinical PH classification and is characterized by chronic pulmonary artery obstructions by thromboembolic material 1,4,5 . Following the announcement of SARS‐CoV‐2 infection as a pandemic on March 11, 2020 by the World Health Organization (WHO), 6 different PH centers in Europe and the United States reported higher hospitalization and mortality rates due to COVID‐19 among PAH/CTEPH patients than in the general populations 7–13 . This may be due to the underlying medical conditions—namely chronic lung diseases and/or coronary heart diseases—and/or the reduced visits to PH centers during the pandemic, which delayed PH diagnosis and early detection of disease progression 8,12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased susceptibility to PAH may only occur in those who survive severe COVID-19, or in those who develop mild or no symptoms of SARS-CoV-2 infection. The results of an Italian study showed that the incidence of COVID-19 in patients with PAH was comparable to that of the general population but consistent with other chronic diseases and a higher risk of death [ 75 ]. Researchers reported a severe case of SARS-CoV-2 infection without the underlying conditions for PAH who developed PAH two months after being discharged [ 70 ].…”
Section: Role Of Sars-cov-2mentioning
confidence: 95%
“…The Italian Pulmonary Hypertension Network noted 100% mortality in their hospitalized cohort early in the pandemic, while the French PH network demonstrated 41.3% in hospital mortality and 24.6% overall mortality. 115 116 Both mRNA and viral vector type COVID-19 vaccines are noted to be safe in patients with PAH. 117…”
Section: Adjunctive and Supportive Therapiesmentioning
confidence: 99%